PENGARUH PENGEMBANGAN DESA BUDAYA KERTALANGU TERHADAP PENDAPATAN PETANI DI DESA KESIMAN KERTALANGU - Engge, Magdalena; Yudiarini, Nyoman; Yuniti, I Gusti Ayu Diah (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
The place of the research is the cultural village of Kertalangu, east Denpasar subdistrick, this research lasted for 3 months from November 2019 to Januari 2020. This study aims to determine the effect of the development of the Kertalangu culture village on the income of farmers in the village of kesert Keralangu east Denpasar District. sub-ditrict, the determination of respondents using the census sampling medhod with 57 respondents. The data analysis method used is the F test and T test methods. The results showed that the influence of the development of the Kertalangu culture village on farmer’s income partially agriculture (X1) had a positive and significant effect on farmers income (Y) that partirially jogging track (X2) had positive ad significant effect on farmers income (Y), culinary testing (X3) positive effect on farmers income (Y), testing of creative space in the economy (X4) have a positive effect on farmer income (Y). The influence of the development of Kertalangu culture village on farmers income simultaneously has a positive and significant effect on farmers income.